Peran Ukuran Perusahaan dalam Memoderasi Pengaruh Financial Distress dan Growth Opportunity terhadap Accounting Prudence - Alexander Giovani; Sugiyanto Sugiyanto (Universitas Galuh, 2026)
This study aims to examine and explore empirical evidence regarding the role of firm size as a determinant that potentially moderates the magnitude of the effects of financial distress and growth opportunity on accounting prudence. The research focuses on entities in the healthcare sector listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using a purposive sampling technique, resulting in 100 observations that met the inclusion criteria. The study adopts a quantitative approach, utilizing secondary data in the form of annual reports collected through documentation methods. The analysis is conducted using panel data regression, allowing for the simultaneous estimation of cross-sectional and time-series effects. The empirical results indicate that financial distress has a negative and significant effect on accounting prudence, whereas growth opportunity does not have a significant effect on the dependent variable. Furthermore, firm size is not supported as a moderating variable capable of altering the relationship between financial distress and accounting prudence or the relationship between growth opportunity and accounting prudence.